DAMPAK PSIKIS PESERTA DIDIK SMP NEGERI 1 MARTAPURA TERHADAP PEMBELAJARAN PJOK DI SIANG HARI - Giriyanto, Ega Bintang; Nurdiansyah; Edwin Wahyu Dirgantoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The influence of PJOK learning hours on the psyche of students also needs to be considered. PJOK learningthat is carried out during the day can make studentsfeel tired and less motivated. This study aims todetermine the psychological impact of SMP Negeri 1Martapura students on PJOK Learning during the day.The research sample used in this study consisted of157 students of SMP Negeri 1 Martapura consisting ofclasses VII B, VIII A, VIII C, IX F, IX G. This type ofresearch is quantitative descriptive. The data collectioninstrument uses a questionnaire that is distributed tothe students. From the results of the study, it wasobtained that the majority of students' psychologicalimpact on PJOK learning during the day was in the high category, which was 104 people or 66.2% of thetotal sample of 157 students. Other results were 31people or 19.7% in the medium category and 20people or 12.7% were in the very high category. This iscertainly a problem where only 2 people or 1.3% are inthe low category.